Understanding the Effects of Material Properties on Nanoindentation Responses Through Data Analysis - Hu, Zhong; Hu, Yuchi (Micro and Nanosystems, 2021)
Background: Nanoindentation is arguably the most versatile and effective method for measuring materials’ mechanical properties at nanoscale. However, due to the complexity of the deformation process during the nanoindentation tests, many experimental factors can significantly affect the nanoindentation results. Objective: This research aims to investigate the quantitative effects of material properties on nanoindentation responses and apply these relationships to the evaluation of broader material properties through nanoindentation. Methods: This study uses intensive computer modeling based on finite element analysis and modeling data analysis through curve fitting. Results: Nanoindentation responses (indentation load versus depth data) were numerically modeled by computer modeling, considering the effects of the mechanical properties of the materials (low-carbon steel AISI1018, steel alloy AISI4340, and aluminum alloy 6061-T6) and the indenter geometries (Berkovich, cylindrical, and spherical indenters). Through data analysis, the quantitative relationships between indentation load and indentation depth were established. The parameters in the formulae were optimized by the least-squares method, and high accuracy of the correlation coefficients between the modeling results and the formulae was achieved. Conclusion: It was found that the parameters of the formulae directly reflect the material properties of a testing specimen, and more material properties can be estimated through nanoindentation.
Keywords: cylindrical indenter